ANALISIS HAMBATAN DAN STRATEGI KOMUNIKASI ANTAR PRIBADI ANAK PANTI ASUHAN YATIM MUHAMMADIYAH KARANGANYAR - Firdaus, Muskaf Al (JURNAL KOMUNITAS, 2017)
Communication is currently one of the main individual factors to remain adaptable and acknowledged. Communication changes in accordance with their needs. The reasons relate to communicate need, communicate objectives, interests taken from communicating and the why a person should be sociable and communication are the developments in communication. Interpersonal communication is one ofinteract way ofPanti Asuhan Yatim Muhammadiyah Karanganyar (PAYM). Therefore, in daily communication will be found some resistance of communication. The aims of this study is to determine the resistance occured and to explain and also to describe strategies in overcoming the resistanc that happened in PAYM. This study useddescriptive qualitative method. The data used in this study was the result of observation, questionnaires and interviews to children at PAYM and documents that support the existence of the reformatory. The data analysis used was interactive data analysis model. The results of this study indicates that the resistanceoccurred in PAYM are (1) Prejudice, (2) Messaging, (3) Feedback, (4) Semantics, (5) Symbol (6) Psychological, (7) Physical. The implementation of the strategy of handling these resistance can be shown by: (1) Trust strategy can be used toward prejudice and semantics resistance, (2) Means strategy it can be used in physical resistance, (3) Clarity strategieswas useful in messaging, symbol , prejudice, physical, and psychological, (4) Consistency strategyis used when physical semantic and psychological arise, (5) Ability strategycan be used when physical resistance exist, (6) Context strategy is helpful in symbol, physical, feedback occurs resistance and (7) Content strategy can be used when physical barriers and message delivery occurs